Analysis of external resources in agricultural production - Jiménez-Velázquez, Mercedes A.; González- Burgos, Gerardo (Revista Mexicana de Ciencias Agrícolas, 2017)
This paper is oriented to analyze the investment of external resources (remittances) for agricultural production; through programs aimed at promoting rural development. The aim of the study is to identify transformations, aimed at proposing productive projects with technological innovations in producers who adopt them in terms of knowledge, social, organizational and economic relations to improve their social welfare. The research was carried out with agricultural producers in the community of San Pablo Güila, Municipality of Santiago Matatlán, Oaxaca. Methodology was used with a mixed approach: quantitative, applying a questionnaire to heads of families of Zapotec origin; and qualitative studies using social research techniques: direct and participatory observation. Results evidenced changes in production, family and group organization, reflecting that the external support received by migrant relatives living in the United States of America, its destination is linked to the investment on the productive project and affects the way of thinking of the producer, Promotes training and food that tends to a socioeconomic, educational, productive and technological improvement. The importance of the role of remittances in improving the standard of living is perceived.